PWE-189 Achieving high quality colonoscopy: using graphical representation to measure performance and reset standards. (28th May 2012) - Rajasekhar, P T; Rutter, M D; Bramble, M G; Wilson, D W; East, J E; Greenaway, J R; Saunders, B P; Lee, T J; Barton, R; Hungin, P; Rees, C J; ,
Abstract : Introduction: The aim of colonoscopy is to examine the colon completely and meticulously looking for malignant and pre-malignant lesions (adenomas). The measure for completeness is the caecal intubation rate (CIR) and for thoroughness the adenoma detection rate (ADR). National Standards (NS) are ≥90% and ≥10% respectively. 1 Variability in CIR, ADR and thusly quality, have been shown but comparison between individuals and units is difficult. 2 3 We aimed to use graphical representation to assess colonoscopy performance in the North East of England. Methods: Data on colonoscopy performance and sedation use were collected over 3 months from 12 units. Colonoscopies performed by screening colonoscopists were included in the global CIR only. Funnel plots with upper and lower 95% confidence limits (CL) for CIR and ADR were created using the binomial probability distributions for inferences about a single proportion. Results: CIR was 92.5% (n=5720) and ADR 15.9% (n=4748). All units and 128 (99.2%) colonoscopists were above the lower limit for CIR. All units achieved the ADR standard with 10 above the upper limit. Ninety-nine (76.7%) colonoscopists were above 10%, 16 (12.4%) above the upper limit and 7 (5.4%) below the lower limit (Abstract PWE-189 figure 1 ). Median medication doses were: 2.2 mg midazolam, 29.4 mg pethidine, and 83.3 mg fentanyl. 15.1% of colonoscopies were unsedated. Complications were bleeding (0.10%) and perforation (0.02%). There was 1 death possibly related to bowel preparation. Conclusion: Results indicate colonoscopies are performed safely and to a high standard. Funnel plots can highlight variability and areas for improvement. Analyses of ADR presented graphically around the global mean suggest that the NS should be reset at 15%. Competing interests: None declared. References: 1. The Joint Advisory Group for Gastrointestinal Endoscopy . Guidance for colonoscopy certification and continued practice. Dr Colin Rees and Dr John Painter. 2006. http://www.thejag.org.uk 2. Bowles CJ, Leicester R, Romaya C. A prospective study of colonoscopy practice in the UK today: are we adequately prepared for the national colorectal cancer screening tomorrow? Gut 2004;53 :277–83. 3. van Rijn JC, Reitsma JB, Stoker J, et al. Polyp miss rate determined by tandem colonoscopy: a systematic review. Am J Gastroenterol 2006;101 :343–50.